Triagem de mutações no gene COL1A1 em pacientes com osteogênese imperfeita - Moraes, Marcos Vinícius Dornelas de (2011)
Osteogenesis Imperfecta (OI) is a heritable disorder associated with bone fragility and propensity to fracture. The most common mutations associated with dominant inheritance affect the structural genes of type I collagen and can result from failure to synthesize the products of COL1A1 or COL1A2 genes (quantitative) or by substitution for glycine residues within the Gly-X-Y triplet domain of the triple helix (qualitative). The aim of this study was to verify the occurrence of pathogenic mutations in coding regions of the COL1A1 gene, including splice sites and exon flanking regions, in patients with Osteogenesis Imperfecta assisted at the Hospital Infantil Nossa Senhora da Glória, Vitória - ES.